2015
DOI: 10.17576/ajag-2015-6-01
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Kawalan Dalaman, Sokongan Pengurusan dan Keberkesanan Audit Dalaman Sektor Awam Di Malaysia

Abstract: The objective of this study is to examine the relationships between the effectiveness of internal control system (ICS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Further, Badara and Siti (2014) examine the relationship between effective internal control system and internal audit effectiveness at local government level yet their study are only exploratory in nature at local government level. In the latest research, Hassan et al (2016) support the fact that the effectiveness of internal control system and support management can improves the effectiveness of public sector internal audit in Malaysia. Further, their findings also revealed that management support plays an important role in enhancing the relationship between the effectiveness of the internal control system and the effectiveness of internal audit.…”
Section: Effectiveness Of Internal Control Systemmentioning
confidence: 83%
See 3 more Smart Citations
“…Further, Badara and Siti (2014) examine the relationship between effective internal control system and internal audit effectiveness at local government level yet their study are only exploratory in nature at local government level. In the latest research, Hassan et al (2016) support the fact that the effectiveness of internal control system and support management can improves the effectiveness of public sector internal audit in Malaysia. Further, their findings also revealed that management support plays an important role in enhancing the relationship between the effectiveness of the internal control system and the effectiveness of internal audit.…”
Section: Effectiveness Of Internal Control Systemmentioning
confidence: 83%
“…According to Chenhall (2003), contingency theory is a theory of behavior and its variables consist of environment, technology, size, organizational structure, strategy and culture. Hassan et al (2016) argue that the structure of organization's internal control system will affect the performance of the organization (internal audit performance). In this context, the effectiveness of internal control system consists of five components is an example of organizational structure variables.…”
Section: Effectiveness Of Internal Control Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, contact management strategies have become important due to workplace changes, the evolution of expectations of the communication system and communication knowledge, as well as the actual realities of the business (Walker, 2011). Hassan et al (2015) have concluded that the assistance from management plays an important role in strengthening the relationship between the efficiency of internal audit, which is directly connected to the execution of contact activities. As such, it does not only offer employees the ability to display their current abilities but also increases the confidence among staff to attempt new tasks.…”
Section: Introductionmentioning
confidence: 99%